Analisis Dampak dan Adaptasi Masyarakat terhadap Bencana Lingkungan Akibat Tambang Galian C di Desa Korleko Selatan Kecamatan Labuhan Haji - Widiya Ayu Agustina; Hasrul Hadi; Baiq Ahda Razula Apriyeni (Mataram University, 2026)
This research aims to analyze the physical (spatial), social, and economic impacts, as well as how the community adapts to environmental disasters caused by C-mining activities in Korleko Selatan Village, Labuhan Haji District. This study employed a mixed-method approach (descriptive qualitative and spatial analysis based on GIS). Qualitative data collection techniques include observation, interviews, and documentation, while spatial data collection uses direct observation and satellite imagery. Qualitative data analysis techniques used the Miles and Huberman Model (1992), followed by spatial analysis based on QGis with digitization to visualize the distribution of physical impacts of environmental disasters caused by mining activities. The research results showed that the impact of C-mining activities includes interrelated physical, social, and economic effects. The physical impacts include the decline in water quality of the Rumpang River, changes in agricultural land conditions, potential landslides, and road damage. The social impacts include disturbances due to dust, increased farmer concerns, and community conflicts with miners. Then, the economic impact includes the opening of job opportunities and sources of Regional Original Income (PAD), but on the other hand, it causes losses to farmers due to decreased crop yields, which affect their income. The community adapted by adjusting agricultural patterns, changing livelihoods, utilizing alternative water sources, and conducting demonstrations and agreements to mitigate the impact.